Pembuatan Alat Permainan untuk Pembelajaran English for Young Learners di Yayasan Al-Kahfi Cabang Palembang - Nian Masna Evawati; Yusri Yusri; Evi Agustina Sari; Darmaliana Darmaliana; Eli Yeny; Koryati Koryati (Politeknik Negeri Sriwijaya, 2021)
This is the second year of the community service team to assist a private institution, Yayasan Al-Kahfi of Palembang, which provides teaching assistance to the orphan and disadvantage children as one of its mission. English was one of the subjects taught there once in a week. The obstacles faced were the educational background of the instructors which were not linear with the English subject, the lack of experience on how to teach English for young learners, the lack of teaching media, the limited time of teaching English which was only about 50 minutes, and the range of age in the same group that varied from kindergarten to first until third elementary class. Therefore, an effective and efficient teaching and learning strategy was extremely important to be implemented. Since teaching English for young learners should be in a kind of fun and pleasing atmosphere, therefore enjoyable and entertaining activities as one of the strategy can be used for this issue. These kinds of activities made the students unconsciously as if they were playing not studying. Therefore, the team made and modified games rules as the learning media to ease the students in learning English in terms of memorizing the vocabularies and making simple sentences in a fun and pleasing activities. The games proved that the teaching and learning activities can be done extremely effective and efficient.